Metal oxides and carbonaceous nanocomposites as platinum-free counter electrodes for dye sensitized solar cells; A review - Stephen Tenywa; Jude Tadeo Inyalot; Alex Okello (Heliyon, 2025)
Recently, dye-sensitized solar cells (DSSCs) have been considered as a future solution to the increasing energy demand across the globe. This is due to their simple structure, low toxicity, ease of fabrication and promising high-power conversion efficiency (PCE). A standard DSSC is composed of a photo-anode (usually made of TiO2), a counter electrode (CE) made of platinum (Pt), a light sensing dye and an electrolyte. In terms of cell fabrication and materials cost, DSSCs are cheaper as compared to other photovoltaic (PV) cells. However, the use of alternative and in-expensive Pt-free counter electrodes has been a focal area of research for over a decade. In addition, Pt is affected by persistent corrosion when exposed to I−/I3− redox electrolyte. In this review, we focus on analyzing the current status of the performance of DSSCs with metal oxides-based CEs and the Carbonaceous nanocomposites as alternative Pt free CEs for DSSCs. We also highlight the significant contributions made by these materials for effective performance in DSSC. This review is organized as follows; (1) Introduction; (2) Genesis and Advancements of DSSCs; (3) Current Developments in Counter Electrodes (4); Summary and (5); Perspective, in which we highlight the recommendations. The various synthesis methods for material preparation, their advantages and disadvantages are also reviewed. Lastly, the available possibilities for further research targeted at acquiring best performing DSSCs are highlighted.